The role of Candida species in the occurrence of dental caries in Thi Qar Governorate - Waheeb, Emaduldeen Hatem Abed; Mohammed Hashim AL-Yasiri,; Afrah Abid Maktoof, (University of Thi-Qar Journal of Science, 2023)
Dental caries is a multifactorial disease associated with many factors such as cariogenic microorganisms. Candida is known to be associated with early colonization of cariogenic leading to dental caries. The current study aims to isolation and diagnosis Candida species from caries lesions and the surrounding dental plaque in relation to dental caries. This study was conducted during July 2021–December 2022 in Thi-Qar governorate. Samples were collected from 100 patients using sterile procedures for ages from 4 to 65 years for both genders for various factors such as daily intake of sweets, daily brushing of teeth and smoking. Eighty three Candida isolates of six species were isolated, C. albicans was 44, C. glabrata 11, C. dubliniensis 14, C. tropicalis 10, C. krusei 3 and C. utilis 1, in all age groups and for both genders. The current study proved the existence and role of different species of Candida in causing caries disease, not just C. albicans.